Hypericum triquetrifolium and H. neurocalycinum as Sources of Antioxidants and Multi-Target Bioactive Compounds: A Comprehensive Characterization Combining In Vitro Bioassays and Integrated NMR and LC-MS Characterization by Using a Multivariate Approach - Stefano Dall'Acqua; Gunes Ak; Kouadio Ibrahime Sinan; Fevzi Elbasan; Irene Ferrarese; Stefania Sut; Evren Yıldıztugay; Gregorio Peron; Elisabetta Schievano; Marie Carene Nancy Picot-Allain; Mohamad Fawzi Mahomoodally; Gokhan Zengin (Frontiers Media S.A., 2021)
Hypericum triquetrifolium and H. neurocalycinum were evaluated for their phytochemical content and in vitro bioactivity. NMR analyses were performed on the methanol extract of the aerial parts of H. triquetrifolium to establish the main classes of phytoconstituents. Then, LC-DAD-MSn analyses were performed in order to compare the composition of aerial parts and roots extracts of both Hypericum species, obtained using either methanol or water as solvents. Results, processed using multivariate data analysis, showed a significantly higher phenolic content of methanol extracts compared to water extracts, while minor qualitative differences were observed between the two. Distinctive flavonoid and PAC patterns were observed for H. triquetrifolium and H. neurocalycinum, and specific compounds were exclusively detected in one or the other species. Specifically, the phloroglucinols 7-epiclusianone, hyperfirin and hyperforin were present only in H. neurocalycinum, while hyperforin was detected only in H. triquetrifolium. Extracts were assayed using different in vitro tests to evaluate their antioxidant properties and their inhibitory activity against several enzymes, showing significant antioxidant and metal chelating activities. Furthermore, inhibitory properties against acetylcholinesterase, butyrylcholinesterase and tyrosinase were observed. Multivariate approaches were used to correlate biological data with the phytochemical composition of the different extracts. The results, showing positive correlations between specific chemical constituents and the measured bioactivities, represent preliminary data that could guide future studies aimed at isolating bioactive constituents from H. neurocalycinum and H. triquetrifolium for further pharmacological evaluations.